Dr. Rodrigo Fernández Pellón — Deep Plane Facelift — Madrid - Fernández Pellón, Rodrigo (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Rodrigo Fernández Pellón, practicing in Madrid, Spain. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003332; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; spain; madrid